SIFAT OPTIK DAN PERMITIVITAS LISTRIK MEMBRAN POLIMER PADAT KITOSAN/PEO - Kartika Sari; Sunardi Sunardi; Agung Bambang Setio Utomo; Parmin Lumban Toruan; Evi Yulianti; Mashadi Mashadi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Synthesis and characterization of the chitosan/PEO solid polymer membranes were carried out to determine the morphological structure, crystal structure and functional groups. Synthesis of the chitosan/PEO solid polymer membrane was carried out by solution casting method. Characterization was performed using the FTIR (Fourier Transform Infra Red), XRD (X-ray Diffraction), SEM (Scanning Electron Microscopy) and EIS (Electrochemical Impedance Spectroscopy). The FTIR results showed that the chitosan/PEO solid polymer membrane interacted with the –OH and C-H functional groups at wave numbers 1500 - 945 cm-1 and formed a bending bond between functional groups of the C-C and –NH3. The SEM results showed that the homogeneous agglomeration was formed on the membrane surface due to the addition of PEO powder. This causes the formation of bonds between atoms to unstable. The XRD results obtained that the chitosan/PEO solid polymer membrane pattern tended to have a semicrystalline structure. The graph of the EIS results shows the electric permittivity does not form a semicircular arc. There was no grain response on the chitosan / PEO solid polymer membrane. The results of SEM, XRD, FTIR and EIS characterization show that chitosan /PEO solid polymer membranes can be used as an alternative to solid polymer electrolytes.